PADANAN YAKUWARIGO DALAM BAHASA SAMURAI - Yestati Novia Rullis; Arza Aibonotika; Dini Budiani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study aims to discuss the synonyms of yakuwarigo in the manga Rurouni Kenshin. Yakuwarigo is a special arrangement of expressions or ways of speaking that tell a character in a fictional story. The method used is descriptive qualitative, the data in this study were obtained by observing and analyzing the manga Rurouni Kenshin volumes 1 and 2. The results of this study indicate that the synonyms of yakuwarigo such as pronouns, copulas, forms of negation, greetings, expressions of apology and expressions of forgiveness when paired into language Indonesia no longer gives an exclusive impression as a samurai, there are copulas that do not have an synonym in Indonesian.Key Words: Yakuwarigo, Synonyms, Rurouni Kenshin manga